The effect of conventional transcutaneous electrical nerve stimulation on somatosensory evoked potentials - (:unkn) unknown (My University, 1995)
Transcutaneous electrical nerve stimulation (TENS) is an electrotherapeutic modality used for analgesia. We planned to demonstrate selective stimulation of large diameter fibers with conventional type TENS by way of somatosensory evoked potentials (SEP). We have analyzed index finger-wrist segment median nerve sensory potential and SEP recordings obtained from C2 and Cc before TENS and at 5, 10 and 15 minutes of TENS application of 14 adult healthy volunteers. SEP and finger-wrist segment sensory nerve conduction amplitudes were significantly decreased compared to pre-TENS values during 5, 10, and 15 minutes of TENS application (p < 0.05). These results reflect the selective stimulation of large diameter afferent fibers of conventional type TENS.
Keywords: Adult; Female; Humans; Afferent Pathways; Male; Time Factors; Nerve Fibers; Neural Conduction; Spinal Cord; Cervical Vertebrae; Sensation; Median Nerve; Fingers; Wrist; Analgesia; Evoked Potentials, Somatosensory; Neurophysiology; Somatosensory Cortex; Transcutaneous Electric Nerve Stimulation